STRATEGI PENANGANAN RISIKO OPERASIONAL PEMASARAN BERAS PADA PB. SELARAS MAKMUR TRIJAYA - Juni Trisnowati; Giarti Slamet; Dewi Pujiani (LPSDI Bina Patria, 2022)
Rice in Indonesia is positioned as a strategic commodity, both from an economic and socio-political perspective, because rice is a staple food for 95% of the Indonesian population, provides employment opportunities and a source of income for around 21 million farming households, and about 30% of the total expenditure of poor households. allocated to rice. Micro, small and medium enterprises (MSMEs) are businesses that play an important role in the national economy. Currently, MSMEs are run in various regions in Indonesia. One of the areas that run this business is Karawang, one of which is in the field of rice marketing. Marketing strategy is a form of plan to support a company in marketing its products. MSME Selaras Makmur Trijaya is one of the rice milling factories. These businesses want to expand their market. Therefore, the right marketing strategy is needed from the results of understanding the strengths and weaknesses, as well as opportunities and threats to expand the distribution area to outside its territory. risk indication is the first step to look at marketing operational problems at PB Selaras Makmur Trijaya. By using the Z-Score and ValueMethod in Danger (VAR), it will show the results of the probability and impact of marketing operational risk. Prevention and mitigation strategies can be this company's responsibility for the expected sales growth.